The Depletion of Carbohydrate Metabolic Genes in the Gut Microbiome Contributes to the Transition From Central Obesity to Type 2 Diabetes - Jia, Ruikai; Huang, Min; Qian, Lichun; Yan, Xiaoye; Lv, Qing; Ye, Hua; Ye, Li; Wu, Xin; Chen, Weizhi; Chen, Ye; Jia, Yankai; Huang, Yueqing; et al. (Frontiers in Endocrinology, 2021)
Obesity, especially central obesity, is a strong risk factor for developing type 2 diabetes (T2D). However, the mechanism underlying the progression from central obesity to T2D remains unknown. Therefore, we analyzed the gut microbial profiles of central obese individuals with or without T2D from the Chinese population. Here we reported both the microbial compositional and gene functional alterations during the progression from central obesity to T2D. Several opportunistic pathogens were enriched in obese T2D patients. Also, we characterized thousands of genes involved in sugar and amino acid metabolism whose abundance were significantly depleted in obese T2D group. Moreover, the abundance of those genes was negatively associated with plasma glycemia level and percentage of individuals with impaired plasma glucose status. Therefore, our study indicates that the abundance of those depleted genes can be used as a potential biomarker to identify the central obese individuals with high risks of developing T2D.